Changing sleep architecture through motor learning: influences of a trampoline session on REM sleep parameters - Erlacher, Daniel; Schmid, Daniel; Zahno, Stephan; Schredl, Michael (Life, 2024)
Previous research has shown that learning procedural tasks enhances REM sleep the following night. Here, we investigate whether complex motor learning affects sleep architecture. An experiment in which twenty-two subjects either learned a motor task (trampolining) or engaged in a control task (ergometer) was carried out in a balanced within-group design. After an initial laboratory adaptation night, two experimental nights were consecutive. The results indicate that learning a motor task had an effect on REM sleep parameters and, therefore, support the hypothesis that learning a procedural skill is related to an increase in REM sleep parameters. However, the statistical effect on REM sleep is smaller than found in previous studies. One might speculate that the motor learning was not intense enough compared to other studies. For sports practice, the results suggest that REM sleep, which is particularly rich in the morning, plays an important role in motor memory consolidation. Thus, this phase should not be interrupted after complex motor skill learning sessions. In future studies, other motor tasks should be applied.